Prevalence of Sexually Transmitted Infections in a Tertiary Care Centre - Karn, D; Amatya, A; Aryal, E R; KC, S; Timalsina, M (Kathmandu University Medical Journal, 2012)
Background The burden of sexually transmitted infections is huge and is disproportionately affecting developing nations. In Nepal, recent available data on sexually transmitted infections are mostly targeted to high risk population. A prevalence study was thus done to explore the pattern of sexually transmitted infection syndromes among general population of Nepal. Objectives To highlight the prevalence and changing pattern of sexually transmitted infections among general population. Methods A retrospective study. The study was conducted among 145 patients attending Department of Dermatology and Venerology, Dhulikhel Hospital Kathmandu University Hospital, for voluntary counseling and testing from April 2010 to April 2011. Syndromic case management approach was used for the classification and treatment of the patients. Results 106 patients were suffering from Sexually Transmitted Infections and 2 patients were positive for Human Immunodeficiency Virus. The most common diagnosis was genital viral infections (41.7%). Prevalence was highest among drivers/conductors (26.9%) and migrating workers (23.1%). Age group 20 to 24 years was the maximum sufferers (37%). Unsafe sexual activity (66.7%) was the most potential exposure and majority of the patients were not consistent in using condom. Conclusions Genital viral infections constitute the major bulk of sexually transmitted infections. Majority of the patients suffering from sexually transmitted infections were in the age group 20 to 24 years and were mostly drivers, conductors or migrating workers by occupation. In the background of few available baseline data, the results are expected to assist successful target interventions in the near future. DOI: http://dx.doi.org/10.3126/kumj.v9i2.6287 Kathmandu Univ Med J 2011;9(2):44-8